The Role of Interpersonal Uncertainty in Prosocial Behavior - Anujit Chakraborty; Luca Henkel (Institute of Labor Economics (IZA), 2025)
In prosocial decisions, decision-makers face interpersonal uncertainty–uncertainty about how their choices impact others' utility. We use three approaches to show how it shapes classic patterns of prosocial behavior like ingroup favoritism, merit-based fairness, and self-favoring behavior. First, we compare standard allocation decisions with decisions where we remove social consequences but retain uncertainty, revealing strikingly similar patterns across both. Second, we exogenously vary interpersonal uncertainty to estimate the aversion to interpersonal uncertainty and quantify how it combines with preferences to determine prosocial decisions. Finally, we show that self-reported interpersonal uncertainty systematic ally predicts behavior across individuals, choice patterns, and behavioral interventions.
Keywords: C91; D01; D91; 330; prosocial behavior; decision-making under uncertainty; interpersonal uncertainty; ingroup favoritism; merit-based fairness; self-favoring behavior